If \[\alpha ,\beta \] are the zeroes of the polynomials \[2{{y}^{2}}+7y+5\], then find the value of \[\alpha +\beta +\alpha \beta \].
Answer
Verified
408.9k+ views
Hint: We are given the zeros of the polynomial \[2{{y}^{2}}+7y+5\], which are, \[\alpha ,\beta \]. So, first we have to figure the values of these zeroes and then we have to find the value of \[\alpha +\beta +\alpha \beta \]. So, in order to figure out the values of the zeroes, we will use the formula for sum of the zeroes and the product of zeroes. The given polynomial is of the form \[a{{y}^{2}}+by+c\]. So , Sum of zeroes = \[\alpha +\beta =-\dfrac{b}{a}\] and the product of zeroes = \[\alpha \beta =\dfrac{c}{a}\]. Then, we will have the values of the zeroes and we will substitute these in the expression \[\alpha +\beta +\alpha \beta \] and get the value of the expression. Hence, we will have the required value of the expression.
Complete step-by-step solution:
According to the given question, we are given the zeros of a polynomial \[2{{y}^{2}}+7y+5\] and we are asked to find the value of \[\alpha +\beta +\alpha \beta \].
The polynomial that we have is,
\[2{{y}^{2}}+7y+5\]
It is of the form, \[a{{y}^{2}}+by+c\] and so we get the corresponding values of a, b and c as,
\[a=2,b=7,c=5\]
We are given that \[\alpha ,\beta \] are the zeroes of the polynomial. So, we will first figure out the value of these zeroes and then we will find the value of the expression.
So, we have,
Sum of the zeroes = \[\alpha +\beta =-\dfrac{b}{a}\]
\[\Rightarrow \alpha +\beta =-\dfrac{7}{2}\]
Next, we have,
The product of zeroes = \[\alpha \beta =\dfrac{c}{a}\]
We get.
\[\Rightarrow \alpha \beta =\dfrac{5}{2}\]
Now, we can find the value of the given expression, that is, \[\alpha +\beta +\alpha \beta \]
So, we get,
\[\Rightarrow \left( \alpha +\beta \right)+\alpha \beta \]
We will now substitute the values in the above expression and we get,
\[\Rightarrow \left( -\dfrac{7}{2} \right)+\dfrac{5}{2}\]
\[\Rightarrow -\dfrac{7}{2}+\dfrac{5}{2}=\dfrac{-2}{2}\]
\[\Rightarrow -1\]
Therefore, the value of the given expression is -1.
Note: The formula of the sum of the zeroes and the product of the zeroes should be correctly and carefully written without getting confused with the terms involved. We do not have to explicitly find the value of the zeroes of the polynomial \[\alpha \] and \[\beta \]. Since, the expression did not require such independent values, so used the values from the sum and the product of the zeroes and directly substituted in the expression given to us.
Complete step-by-step solution:
According to the given question, we are given the zeros of a polynomial \[2{{y}^{2}}+7y+5\] and we are asked to find the value of \[\alpha +\beta +\alpha \beta \].
The polynomial that we have is,
\[2{{y}^{2}}+7y+5\]
It is of the form, \[a{{y}^{2}}+by+c\] and so we get the corresponding values of a, b and c as,
\[a=2,b=7,c=5\]
We are given that \[\alpha ,\beta \] are the zeroes of the polynomial. So, we will first figure out the value of these zeroes and then we will find the value of the expression.
So, we have,
Sum of the zeroes = \[\alpha +\beta =-\dfrac{b}{a}\]
\[\Rightarrow \alpha +\beta =-\dfrac{7}{2}\]
Next, we have,
The product of zeroes = \[\alpha \beta =\dfrac{c}{a}\]
We get.
\[\Rightarrow \alpha \beta =\dfrac{5}{2}\]
Now, we can find the value of the given expression, that is, \[\alpha +\beta +\alpha \beta \]
So, we get,
\[\Rightarrow \left( \alpha +\beta \right)+\alpha \beta \]
We will now substitute the values in the above expression and we get,
\[\Rightarrow \left( -\dfrac{7}{2} \right)+\dfrac{5}{2}\]
\[\Rightarrow -\dfrac{7}{2}+\dfrac{5}{2}=\dfrac{-2}{2}\]
\[\Rightarrow -1\]
Therefore, the value of the given expression is -1.
Note: The formula of the sum of the zeroes and the product of the zeroes should be correctly and carefully written without getting confused with the terms involved. We do not have to explicitly find the value of the zeroes of the polynomial \[\alpha \] and \[\beta \]. Since, the expression did not require such independent values, so used the values from the sum and the product of the zeroes and directly substituted in the expression given to us.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE